PLS-SEM analysis: Tri Nga moderates determinants of accounting fraud - Ayem, Sri; Azka, Sabila Amidda (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
The study aims to investigate the impact of love of money and rule of law on accounting fraud and the role of Tri Nga (ngerti, ngrasa, nglakoni) as a moderator. This study used a survey method with quantitive approach. The data was collected involving accounting students in all universities in Indonesia that selected by snowball sampling method. PLS-SEM analysis was employed for the hypothesis testing using the SmartPLS. The results revealed love of money significantly affects accounting fraud. Rule of law significantly affects accounting fraud. Tri Nga significantly affects accounting fraud. Tri Nga moderates between love of money on accounting fraud. But, Tri Nga could not moderate between rule of law and accounting fraud. This study is expected to contribute the accounting fraud literature through fraud triangle theory and provide direction on the importance of strengthening moral values and law enforcement as a preventive measure of accounting fraud.